Dificuldades na leitura entre alunos do 1º e 3º ano de uma escola pública de Igarapé-Açú-PA: uma análise a partir do discurso docente - MARTINS, Ed Nilse Pinheiro (2019)
Difficulties in reading between students from 1st to 3rd year of a public school in Igarapé-Açu / PA: An analysis from the teaching discourse. The process of learning to read involves numerous difficulties, being relevant its knowledge for a higher quality in the teaching. The purpose of this qualitative study was to understand the role of the teacher in face of the reading difficulties of his students and to identify the main factors that make it difficult to learn the reading of the students from the 1st to 3rd year in the Manoel Henrique da Rocha municipal school. The semistructured interview was used as a tool with the aid of a questionnaire, the participants being two teachers who teach from the 1st to the 3rd year of elementary school. The teachers interviewed expressed that the lack of attention of the children, the inefficiency of the assistance by the parents and the structure of the school are among the main factors that hinder the teaching process. It is believed that this reality can be changed from actions by the families, teachers, school and public policies that value education as something significant and relevant to the emancipation of schooling in this country. The present research achieved the objectives that it proposed.